A Massive Open Online Course on climate change: the social construction of a global problem using new tools for connectedness. (31st July 2014) - Burch, Sarah L.; Harris, Sara E.
Abstract : Climate change is a pervasive and challenging phenomenon that takes on a variety of meanings and frames, each of which suggests different victims, villains, and solutions. New tools are emerging that may facilitate a reframing, or at least the collaborative coproduction, of the climate change conversation. Web‐based social media have provided a new level of connectedness and capacity to collaborate through a merging of the social and educational worlds in the form of Massive Open Online Courses (MOOCs): web‐based, freely available courses taught by university and college instructors, and offered to thousands of students at a time. Our development and delivery of the first interdisciplinary climate change MOOC has opened a new window into (1) the tools available to convene a conversation about climate change, (2) the processes of negotiation, cultural articulation, and identity formation that occur through conversations that include large populations from diverse backgrounds, and (3) the implications of this conversation for the broader climate change discourse, the definition of the problem, attributions of responsibility, and the development of solutions. WIREs Clim Change 2014, 5:577–585. doi: 10.1002/wcc.300 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication Social Status of Climate Change Knowledge > Climate Science and Social Movements